Pengaruh Celebrity Endorser Tasya Farasya Dan Electronic Word Of Mouth Terhadap Keputusan Pembelian Dengan Brand Image Sebagai Variabel Intervening (Studi Pada Mahasiswi FEB Angkatan 2019 Universitas Islam Malang Pengguna Avoskin) - Rifda Nadia Ulya; N Rachma; Alfian Budi Primanto (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This research aims to test and analyz the influence of celebrity endorsers and electronic word of mouth on purchasing decisions with brand image as an intervening variable. The number of samples was determined using the Malhotra formula and the results obtained were 95 respondents. The data obtained by distributing questionnaires to students of the Faculty of Economics and Business Class of 2019 at the Islamic University of Malang who used Avoskin who were selected by purposive sampling. Data analysis in this study used SPSS version 23. Data testing techniques used in this study included validity testing, reliability testing, normality testing, path analysis (path analysis), and research hypothesis testing. The results of this study indicate that Celebrity Endorser and Electronic Word of Mouth have a direct effect on Brand Image, Celebrity Endorser and Electronic Word of Mouth, and Brand Image have a direct effect on Purchasing Decisions, Brand Image plays no role in mediating Celebrity Endorser and Electronic Word of Mouth on Purchasing Decisions. Keywords: Celebrity Endorser, Electronic Word of Mouth, Brand image, Purchase Decision